Perbandingan Arachis pintoi dengan Jenis Tanaman Penutup Tanah Lain sebagai Biomulsa di Pertanaman Kelapa Sawit Belum Menghasilkan - ,, Yuniarti; Chozin, M. Achmad; Guntoro, Dwi; Murtilaksono, dan Kukuh (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Cover crops have the same role as biomulches to maintain soil moisture and reduce the evaporation of soil water. The objective of research was to compare Arachis pintoi versus other cover crops as biomulch in immature oil palm plantations. The study was conducted in the Field of Education and Research Palm IPB-Cargill, Jonggol, Bogor starting in December 2014 until May 2015. The experiment was designed according to a randomized block design with four replications. The treatments were cover crop species (biomulch) i.e. no biomulch/natural vegetation, Arachis pintoi Karp. & Greg., Centrosema pubescens Benth., Calopogonium mucunoides L. and Pueraria javanica Benth. Planting materials used were cutings of A. pintoi and seed of C. pubescens, C. mucunoides and P. javanica. The planting material were planted in plots 9 m x 3 m and plot for biomass 1 m x 1 m. The results showed that the A. pintoi was not significantly different from other biomulches for ground covering and capability to hold water. Soil water content in the treatment of A. pintoi biomulch was not different from other biomulch treatments.